2019
DOI: 10.1111/zph.12633
|View full text |Cite
|
Sign up to set email alerts
|

Occupational swine exposure and Hepatitis E virus, Leptospira, Ascaris suum seropositivity and MRSA colonization in Austrian veterinarians, 2017–2018—A cross‐sectional study

Abstract: We investigated the prevalence of Hepatitis E Virus (HEV), Leptospira and Ascaris suum (A. suum) seropositivity, and of nasal methicillin‐resistant Staphylococcus aureus (MRSA) colonization among Austrian practising veterinarians, and assessed the association with occupational swine livestock exposure. The 261 participants completed a questionnaire on demographics, intensity of occupational swine livestock contact and glove use during handling animals and their secretions. Participants' blood samples were test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 38 publications
(45 reference statements)
0
4
0
1
Order By: Relevance
“…derived from pigs, as well as a high percentage of hybrids, and thus, ascariasis has been characterized as a zoonosis in these regions [36,[39][40][41]. These reports strongly point to the zoonotic potential of A. suum [6,38,42],…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…derived from pigs, as well as a high percentage of hybrids, and thus, ascariasis has been characterized as a zoonosis in these regions [36,[39][40][41]. These reports strongly point to the zoonotic potential of A. suum [6,38,42],…”
Section: Discussionmentioning
confidence: 99%
“…derived from pigs, as well as a high percentage of hybrids, and thus, ascariasis has been characterized as a zoonosis in these regions [36,[39][40][41]. These reports strongly point to the zoonotic potential of A. suum [6,38,42], and the ability of A. suum to develop infection in experimentally infected humans has already been demonstrated [43].…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
“…Several reports in industrialised countries support a link between presence of anti-HEV and direct contact with pigs. Studies in United States [ 61 ], Switzerland [ 62 ], Germany [ 63 ], Australia [ 64 ] found significant differences in prevalence of individuals in close contact with pigs compared to those not exposed. On the contrary other studies conducted in Sweden [ 44 ] and Brazil [ 65 ] found no significant differences between those exposed or unexposed to pigs.…”
Section: Discussionmentioning
confidence: 99%
“…However, the latter may partly stem from the reuse of the same sample sets, especially in older records, for investigating various research questions [61][62][63][64][65][66][67][68] (S3 Info). Remarkably, despite the use of sample sets from Europe as non-endemic negative controls, there were also seven studies that assessed seroprevalence in European regions (e.g., The Netherlands and Austria) [69][70][71][72][73][74][75].…”
Section: Characteristics Of Described Sample Setsmentioning
confidence: 99%